Alteration of the flow distribution at a river bifurcation caused by a system of upstream dams: Case of the Grijalva River basin, Mexico. Issue 2 (3rd November 2021) - Mendoza, Alejandro; Berezowsky, Moisés; Caballero, Christian; Arganis‐Juárez, Maritza
Abstract: Multiple factors control the flow distribution in a river bifurcation. However, one factor that requires further analysis is the effect of upstream reservoirs. Such is the case of the bifurcation of the Mezcalapa River into the Samaria and Carrizal Rivers located in the lowlands of the Grijalva River basin, Mexico. Four dams were commissioned in the upper basin, the first in 1967 and the last in 1987. Since the late 1960s the distribution of the flow at the bifurcation has varied considerably. The flow captured by the Carrizal River between the late 1960s and mid 1980s gradually decreased from 40% to 10%, and later, between the mid 1980s and early 2000s, it increased up to 75%. During the same period, the Samaria River had a reversed pattern. Here, using a two‐dimensional hydro‐morphodynamical model, the impact of an upstream reservoir (that causes homogenization of the flow hydrograph and sediment retention) on bed morphology and flow distribution in a river bifurcation is analyzed. The results indicate that the sediment retention is the factor of largest impact on the flow distribution. The upstream channel incises, and the process propagates to the diffluent with the larger energy gradient developing positive feedback were the erosion increases the hydraulic capacity to capture more flow, resulting in more erosion. The flow homogenization has also an impact. The suppression of peak flows reduces the sediment load capacity in the diffluent with lower energy gradient, generating sedimentation at its entrance and diminishing its hydraulic capacity. Abstract : The effect of a dam on the flow distribution at a river bifurcation is analyzed with a numerical model. The results indicate that the sediment retention produces incision in the upstream channel and then propagates to the diffluent with a larger gradient, developing positive feedback where the erosion increases the hydraulic capacity to capture more flow. Regarding flow homogenization, the suppression of peak flows reduces the sediment load capacity in the diffluent with a lower gradient, generating sedimentation at its entrance.